CHANGES IN THE BIOCHEMICAL CONSTITUENTS OF THE MARINE EDIBLE CRAB, SCYLLA SERRATA AFTER EXPOSURE TO DIMECRON - SAMBASIVA, K.; NAGABHUSHANAM, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1987)
The marine crab Scylla serrara was exposed to Dimecron for 72 hrs, 7.15 and 30 days to study the acute and chronic effect of the pesticide and the changes in protein, lipid and glycogen levels in the gonads, muscle, hepatopancreas and gills were recorded during breeding and non-breeding periods. Observations reveal that protein level increased in gonads, muscle, hepatopancreas and gills during breed ng period, but decreased in all the tissues during non-breeding period, except the gonads An increase in lipid and glycogen levels in muscle and hepatopancreas was observed but decreased in the gonads and gills was recorded during the breeding and non-bleeding periods.